Democracy, the armed forces and military deployment: the 'second social contract' is on the line - Müller, Harald; Fey, Marco; Mannitz, Sabine; Schörnig, Niklas (2011)
Abstract: "The increasing number of troop deployments by democratic states after the end of the Cold War has subjected the 'second social contract' – the (in most cases unwritten) agreement regulating relations between society, government and the armed forces – to new stresses. The authors of this report set out to name the causes and subsequent dangers of this development, urging for future deployment decisions to be more thoroughly and carefully considered. If the democratic responsibility for military deployments is not taken seriously, the gap grows between the armed forces and civilian society." (author's abstract)